Revisiting Slavery and Antislavery 2018
DOI: 10.1007/978-3-319-90623-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Moral Economies and Child Labour in Artisanal Gold Mining in Ghana

Abstract: Main purpose/theme of session : This session will focus on the historical and political complexities and ambiguities of defining slavery and its relationship to inequality, exploitation and subordination. It will set up and frame the themes of the conference by exploring what is constructed as the opposite of slavery, the development of the binary between slavery and freedom, and the content of that freedom, particularly in relation to labour and belonging. Speakers from Philosophy and English will consider th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…A key point is that work is understood and experienced in much of the world as a pathway through which children attain maturity and social responsibility, before becoming adults. The present authors have found this extensively in their own research in West Africa (Howard, 2014(Howard, , 2017Maconachie and Hilson, 2016;Okyere, 2017a), and it has been documented widely elsewhere. Heissler (2012), for example, found female migrant labourers in Bangladesh to increase their respect and status amid their families as a result of their work.…”
Section: Anthropology and Sociologysupporting
confidence: 70%
See 1 more Smart Citation
“…A key point is that work is understood and experienced in much of the world as a pathway through which children attain maturity and social responsibility, before becoming adults. The present authors have found this extensively in their own research in West Africa (Howard, 2014(Howard, , 2017Maconachie and Hilson, 2016;Okyere, 2017a), and it has been documented widely elsewhere. Heissler (2012), for example, found female migrant labourers in Bangladesh to increase their respect and status amid their families as a result of their work.…”
Section: Anthropology and Sociologysupporting
confidence: 70%
“…Yet a large body of ethnographic data shows that, in many cases, children are able to prolong their schooling in contexts where it carries hidden or heavy opportunity costs, precisely by working, including in circumstances deemed harmful. Okyere (2017a) has demonstrated this in Ghana with a compelling case study of children working in quarries. His findings are echoed by Maconachie and Hilson (2016) in the context of artisanal mining in Sierra Leone, as well as in case studies from across the African continent assembled by Thorsen and Hashim (2011).…”
Section: Anthropology and Sociologymentioning
confidence: 94%
“…Yet a large body of ethnographic data shows that, in many cases, children are able to prolong their schooling in contexts where it carries hidden or heavy opportunity costs, precisely by working, including in circumstances deemed harmful. Okyere (2017a) has demonstrated this in Ghana with a compelling case study of children working in quarries. His findings are echoed by in the context of artisanal mining in Sierra Leone, as well as in case studies from across the African continent assembled by .…”
Section: Anthropology and Sociologymentioning
confidence: 94%
“…The dominant discourse found in media accounts and the policy world constructs child traf6icking as a case of innocent victim minors tricked or trapped by unscrupulous adults willing to exploit them. Poverty and a racially-encoded 'cultural backwardness' often feature in the narrative, with the implication that non-white populations are yet to evolve appropriate child-rearing strategies and are too poor not to let their children be exploited (Okyere 2018). Predictably, the kinds of policies and projects attached to this discourse are interventionist, top-down, and at times heavily disciplinary.…”
Section: Child Workers In West Africamentioning
confidence: 99%